Pathophysiological and Clinical Significance of Coronary Artery Ectasia - A Review - Md Taimur, Syed Dawood; Khan, Saidur Rahman; Rahman, Md Hasanur; Gomes, Hemanto I; Islam, Farzana; Siddique, Md Abu; Qumruzzaman, KH; Kulsum, Umme; Uddin Sultan, Md Ashraf (University Heart Journal, 2012)
Coronary artery ectasia is a relatively common entity characterized by inappropriate dilatation of the coronary vasculature. The exact mechanism of its development is unknown, but evidence suggests a combination of genetic predisposition, common risk factors for coronary artery disease and abnormal vessel wall metabolism. It frequently coexists with aneurysms elsewhere, mostly involving the aorta. In this review, the flow disturbances that are associated with this condition and the imaging modalities, which can be used for diagnosis and prospective follow-up are described. The prognosis of coronary ectasias is controversialand prospective studies focusing on conservative or invasive strategies to prevent cardiac complications are needed. DOI: http://dx.doi.org/10.3329/uhj.v7i1.10210 UHJ 2011; 7(1): 42-47